Isolation and Structural Characterization of Curcuminoids with Spectral and Chromatographic Techniques - Sap, Ayse; Yaman, Mehmet; Akyuz Turumtay, Emine (Univ Sindh, Natl Centre Excellence Analytical Chemistry, 2023)
Curcuminoids are the active ingredients of Curcuma longa L. and are one of the most researched subjects owing to their biological activities. This study focuses on the structural analysis of curcuminoids isolated from turmeric roots using NMR spectroscopy. Turmeric rhizomes were extracted with methanol and hexane. Curcuminoids were isolated using column chromatography, and preparative HPLC-UV. The structures of the isolated compounds were characterized using FT-IR, UV-Vis, and GC-MS as well as NMR. Spectral and physicochemical data showed that isolated curcuminoids (ar-turmeron, curcumin, demethoxycurcumin, and bisdemethoxycurcumin) were obtained entirely from the turmeric rhizomes. When both isolation methods are compared, it was concluded that the prep-HPLC method is efficient and practical, while column chromatography is cheap and easy. In both methods, efficient and pure curcuminoids could be easily obtained by using the solvent mixtures specified in this study.
Keywords: Turmeric; Curcuminoid; Isolation; NMR; Chromatography